Survey-data: Characteristics that affect Preference of Decision Models for Asset Selection: Decision-making in Practice - Alégroth, Emil (Blekinge Institute of Technology, 2019)
An industrial questionnaire survey where a total of 33 practitioners, of varying roles, from 18 companies are tasked to compare two decision models for asset selection.

The objective of the study was to evaluate what characteristics of decision models for asset selection that determine industrial practitioner preference of a model when given the choice of a decision-model of high precision or a model with high speed.

The dataset was originally published in DiVA and moved to SND in 2024.
Survey-data: Characteristics that affect Preference of Decision Models for Asset Selection: Decision-making in Practice
Keywords: questionnaire survey; enkätundersökning; decision analysis; beslutsanalys; software development; programutveckling; Software Engineering; Programvaruteknik